2009
DOI: 10.1073/pnas.0901280106
|View full text |Cite
|
Sign up to set email alerts
|

Independent evolution of knuckle-walking in African apes shows that humans did not evolve from a knuckle-walking ancestor

Abstract: Despite decades of debate, it remains unclear whether human bipedalism evolved from a terrestrial knuckle-walking ancestor or from a more generalized, arboreal ape ancestor. Proponents of the knuckle-walking hypothesis focused on the wrist and hand to find morphological evidence of this behavior in the human fossil record. These studies, however, have not examined variation or development of purported knuckle-walking features in apes or other primates, data that are critical to resolution of this long-standing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 41 publications
6
129
0
Order By: Relevance
“…[16][17][18][19] supports the argument that many living ape similarities are not homologies (20); thus the ancestral morphotype for both apes and humans [i.e., the "Miocene ape ancestor" (MAA)] would reflect a more primitive, generalized postcranial morphotype and positional behavior [an "ape convergence" (AC) model]. For example, some have argued from differences in African ape wrist morphology that knuckle walking behaviors evolved in parallel (21,22), in which case the LCA must be more primitive. Thorpe et al (23,24) used similar reasoning to assert that hominins did not evolve from a knuckle-walking LCA, but rather one that practiced the hand-assisted, arboreal bipedality observed in living orangutans (Fig.…”
mentioning
confidence: 76%
“…[16][17][18][19] supports the argument that many living ape similarities are not homologies (20); thus the ancestral morphotype for both apes and humans [i.e., the "Miocene ape ancestor" (MAA)] would reflect a more primitive, generalized postcranial morphotype and positional behavior [an "ape convergence" (AC) model]. For example, some have argued from differences in African ape wrist morphology that knuckle walking behaviors evolved in parallel (21,22), in which case the LCA must be more primitive. Thorpe et al (23,24) used similar reasoning to assert that hominins did not evolve from a knuckle-walking LCA, but rather one that practiced the hand-assisted, arboreal bipedality observed in living orangutans (Fig.…”
mentioning
confidence: 76%
“…These authors also found that the shape of the carpals on the ulnar side to be significantly different in Gorilla and Pan, and that these differences could not be accounted for by differences in locomotor pattern during ontogeny in the two taxa. Kivell and Schmitt (2009) found that the development of supposed knuckle walking characteristics in the wrist followed significantly different ontogenetic trajectories in chimpanzees and gorillas and were also found in non-knuckle walking taxa.…”
Section: Evidence For a Knuckle Walking Last Common Ancestormentioning
confidence: 86%
“…Recent research suggests that humans did not evolve from a knuckle-walking ancestor 27 . Instead, the erection of locomotion likely took place in an arboreal environment, similar to the environment in which orangutans live even at present.…”
Section: Discussionmentioning
confidence: 99%